Esporte e escolarização : projetos, biografias e programa Governamental - Silva, André Luiz da Costa e (2016)
The young people who live the situation of school and sports dual career, must attend school, study, conduct tests and schoolwork and participate in school life, at the same time, the sports training career requires regular diary training, travel, participation in competitions and the care required with the body and the psychic state of the athlete. The study presented here, problematizes the relationship constituted between formal schooling and vocational training for the sport of performance experienced by young people who choose to reconcile this dual career in this phase of life. The work we present next, seeks to understand how these kids reconcile or reconciled school career and the career of the sport. To this end, we seek information on two fronts. A front was that of students/athlete benefited of the scholarship program of the Ministry of Sport. Another source of data for understanding the question we want to answer were the biographies of high-level athletes, seeking there too, understanding how these athletes were able to handle the sports career and school career simultaneously and how the family contributed and influenced the development of this double process. When we think of reconciling sport and school looking at the trajectory of the athletes on the biographies, all world champions with a very high sports performance, we realized that despite families value school learning, the sporting results speaks very loudly and made it clear that that person already has a professional life set in sport. Athletes do not hesitate to quit school to devote himself specifically to sports career. The research produced with the students/athlete benefited by the athlete scholarship program of the Ministry of Sport, shows us that the negotiation between the young people, school and sport, happened in different ways. The mechanisms of regular school rules easing appeared discreetly. In some cases, the club, in the figure of the trainer, encouraged the athlete to school attendance and the completion of homework. Success in dual career agreements depends on the goodwill of the parties involved, and so we realized the need for a systematic instrument, so that these agreements no longer happen from the goodwill of the participants, but legally in all its aspects. So, in conclusion this work, we think it is important to point out suggestions to move forward in meeting the needs of the students/athlete involved in dual career situation.